Efficacy and Safety of Nedaplatin in Advanced Breast Cancer Therapy. (20th April 2016) - Pang, Hui; Feng, Ting; Lu, Hailing; Meng, Qingwei; Chen, Xuesong; Shen, Qiang; Dong, Xiaoqun; Cai, Li
ABSTRACT: Purpose: To compare the time-to-treatment failure (TTF), overall survival (OS), overall response rate (ORR), and adverse effects of regimens including nedaplatin- or cisplatin-based chemotherapy for advanced breast cancer (ABC). Methods: A total of 171 patients with ABC (admission between July 2008 and July 2013) were retrospectively analyzed. Patients received either nedaplatin 75 mg/m 2 (arm N; n = 85) or cisplatin 75 mg/m 2 (arm C; n = 86) in combination with other second-generation chemotherapeutic drugs, such as paclitaxel 175 mg/m 2, docetaxel 75 mg/m 2, gemcitabine 1.25 g/m 2, and navelbine 25 mg/m 2 every 21 days (nedaplatin, cisplatin, paclitaxel, docetaxel on day 1; gemcitabine, navelbine on days 1 and 8). The primary endpoint was TTF in each arm; secondary endpoints were OS, ORR, and toxicity. Results: In the assessable patient population, in arm N, median TTF and OS was 13.87 months (95% CI: 11.55–16.19) and 31.53 months (95% CI: 28.42–34.64), respectively, with an ORR of 48.2%. In arm C, median TTF and OS was 8.7 months (95% CI: 5.82–11.59) and 24.87 months (95% CI: 18.98–30.75), respectively, with an ORR of 37.2%. The occurrence of grades 3 and 4 hematologic toxicity was more frequent (45.9% vs. 25.6%, p = 0.003) in arm N than in arm C. However, grade ≥2 nonhematologic toxicity was less frequent in arm N than in arm C (12.9% vs. 46.5%, p = 2.05 × 10 −7 ). Conclusions: Nedaplatin-based chemotherapy regimen was well tolerated and efficiently improved patients' quality of life characterized by prolonged TTF and OS, with a marginal ORR.